Strategi Bertahan Pedagang Barang Bekas Gang Rendah ditengah Maraknya Online Shop - Ita Rosita Wahiyah; Suherman Arifin; Muhammad Ikrom Arasid (Journal of Islamic Entrepreneurship and Business Research, 2024)
This study aims to analyze and examine the resilience of secondhand goods traders in "Gang Rendah" and investigate how this market has sustained its existence despite the proliferation of online shops in the era of modernization and globalization. The research employs a qualitative descriptive method with data collection techniques including observation, interviews, and documentation. The theoretical framework used is Pierre Bourdieu's theory of social practice, encompassing the concepts of habitus, field, and capital. The findings reveal that this secondhand goods trading activity has existed for decades. "Gang Rendah," located in front of Chinese ethnic-owned shops, serves as a marketplace where traders display their goods on mats or tarpaulins. Transactions occur as buyers and sellers interact while squatting or sitting on the pavement. Based on primary data collected through questionnaires and direct interviews with traders, several reasons were identified for the enduring demand for secondhand goods: 1) affordable prices, 2) usability of the items, 3) suitability for consumer needs, 4) enjoyable interactions, 5) interethnic integration, and 6) historical value. The study also highlights that "Gang Rendah" has been operational since the Dutch colonial era. Despite being a secondhand market, the goods offered are of relatively good quality. Traders typically open their stalls from 9:00 AM to 5:00 PM daily. This market demonstrates how a traditional trading system persists in providing economic opportunities and fostering social cohesion amidst modern commercial trends.